2012
DOI: 10.1177/0264619612453105
|View full text |Cite
|
Sign up to set email alerts
|

Listening to voices of children with a visual impairment: A focus group study

Abstract: The purpose of the study was to identify the educational, social and leisure activities and issues that matter to school children and young people with a visual impairment and to compare their lifestyle with fully sighted counterparts. Thirteen focus groups were conducted and the groups were stratified by age, gender, visual status and school location (urban and non-urban). The sessions were audio taped, transcribed verbatim, coded using NVivo software and a qualitative data analysis was carried out to identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
47
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 33 publications
(48 reference statements)
6
47
1
Order By: Relevance
“…116 Understandably, these children and their parents experience major challenges regarding overall development, participation in society, and self-reliance. 59,63,88 Children with visual impairment have their whole lives ahead and, in case of incurable eye or brain diseases, often have no choice but to live with their visual impairment for many years. Therefore, aiming for the highest levels of functioning, participation in society, and quality of life ensures these children's well-being.…”
Section: Introductionmentioning
confidence: 99%
“…116 Understandably, these children and their parents experience major challenges regarding overall development, participation in society, and self-reliance. 59,63,88 Children with visual impairment have their whole lives ahead and, in case of incurable eye or brain diseases, often have no choice but to live with their visual impairment for many years. Therefore, aiming for the highest levels of functioning, participation in society, and quality of life ensures these children's well-being.…”
Section: Introductionmentioning
confidence: 99%
“…Close Circuit Television (CCTV), magnifying glass, screen reader, and screen magnification) [3] were actually problematic for them at most of the time [4] particularly for children [5]. For the reason they do not want to look different between their sighted peers and sometimes they also missing the equipment [6]. In regards to that, an observation conducted at Special Primary School of Visual Impairment, Penang Malaysia found that the low vision learners have to highly concentrate on the audio in order to get the information displayed on the online TC (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…All this time persons with disabilities and impairments tend to be considered by common people as objects of protection, treatment, and aids rather than subjects for some rights [1], [2]. This perspective makes persons with disabilities isolated from common society and placed in exclusive places and facilities.…”
Section: Introductionmentioning
confidence: 99%